Répliques par l’actrice, répliques d’une actrice : Delphine Seyrig dansLe Troisième Concerto (1963) et Le Lys dans la vallée (1970) - Alexandre Moussa (Mise au Point)
This article intends to determine how the presence of the same actress, Delphine Seyrig, allows to consider two TV fictions directed by Marcel Cravenne, The Third Concerto (1963) and Lily in the Valley (1970) as respective replicas of two art-house films: Last Year in Marienbad (Alain Resnais, 1961) and Stolen Kisses (François Truffaut, 1968). Through an analysis of Seyrig’s performance and star image, we mean to expose how those vehicles specifically designed for her recycle the persona she built through her previous roles in movies while adapting it to the aesthetic constraints of the TV medium. But we also mean to investigate the way these films broaden her image, most notably by putting more focus on the point of view of suffering female characters.